Analysis of the preparedness of Ghanaian formal and traditional industries to adopt hazard analysis critical control point (HACCP) and a model for implementing HACCP in traditional pito brewing - Kwakye, Vivian Obema (2011)
A thesis submitted to the Department of Biological Sciences, College of Science, Kwame Nkrumah University of Science and Technology in partial fulfilment of the requirements for the award of Master of Science degree,